(untitled) (ACME, 2023)
The Suonata a 4 al Santo Sepolcro RV 130 and the Sinfonia al Santo Sepolcro RV 169, two twin compositions probably dating from the 1730s, occupy a singular place in Antonio Vivaldi’s instrumental output. The indication of the title “al Santo Sepolcro” (“at the Holy Sepulchre”) leaves no doubt that the two scores are connected with the Passion of Christ and were therefore composed for Easter week; however, the occasion and destination for which they were written remain problematic. On the one hand the reference of the two compositions to the formal and stylistic model represented by the introductory symphony of the “sepulchre”, the particular type of oratorio cultivated from the 1670s in the imperial chapel in Vienna, is evident. On the other hand, the hypothesis of an adaptation of this compositional model to a context other than the Viennese – or at any rate central European – context remains open, and the hypothesis of some possible destinations in the Venetian context is particularly suggestive.